Protesting Power : War, Resistance, and Law. - Boyle, Francis A. (War and peace library., 2007)
In this compelling book, distinguished activist lawyer Francis Boyle sounds an impassioned clarion call to citizen action against Bush administration policies both domestic and international. Boyle, who has spent his career defending civil resisters, offers the only guide available on how to use international law, constitutional law, and the laws of war to defend peaceful non-violent protesters against governmental policies that are illegal and criminal. He focuses especially on the aftermath of 9/11 and the implications of the war on Afghanistan, the war on terrorism, the war on Iraq, the doc.